Effectiveness of simulation-based training for manual small incision cataract surgery among novice surgeons: a randomized controlled trial - Nair, Akshay Gopinathan; Ahiwalay, Chetan; Bacchav, Ashish E.; Sheth, Tejas; Lansingh, Van Charles; Vedula, S. Swaroop; Bhatt, Venudhar; Reddy, Jagadesh C.; Vadavalli, Pravin K.; Praveen, Smita; Wairagade, Nikhilesh Anil; Pettey, Jeff (Scientific reports, 2021)
This study was designed to determine the effect of a novel simulation-based training curriculum for scleral tunnel construction in manual small incision cataract surgery (MSICS) compared with traditional training. In this multicenter, investigator-masked, randomized clinical trial, resident surgeons within 3 months of matriculation with minimal or no prior experience with MSICS were assigned either to simulation-based training, the Experimental Group (EG), or to conventional training, the Control Group (CG). EG residents were trained to perform scleral tunnel construction using a simulation-based curriculum (HelpMeSee Eye Surgery Simulator), while residents in the CG followed institution-specific curriculum before progressing to live surgery. Surgical videos of the first 20 attempts at tunnel construction were reviewed by masked video raters. The primary outcome was the total number of any of 9 pre-specified errors. On average, the total number of errors was 9.25 (95% CI 0–18.95) in the EG and 17.56 (95% CI 6.63–28.49) in the CG ( P = 0.05); the number of major errors was 4.86 (95% CI 0.13–9.59) in the EG and 10.09 (95% CI 4.76–15.41) in the CG ( P = 0.02); and the number of minor errors was 4.39 (95% CI 0–9.75) in the EG and 7.47 (95% CI 1.43–13.51) in the CG ( P = 0.16). These results support that novice surgeons trained using the novel simulation-based curriculum performed fewer errors in their first 20 attempts at tunnel construction compared to those trained with a conventional curriculum.